Strategi Humas Museum Kehutanan Manggala Wanabakti Jakarta Dalam Meningkatkan Minat Pengunjung Museum - Utomo, Ichsan (LPPM Universitas Bina Sarana Informatika, 2020)
This research is a research on how to use SWOT analysis in advancing an organization. The formulation of the problem in this research is